1999
DOI: 10.1002/(sici)1097-4547(19990301)55:5<629::aid-jnr10>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Death of PC12 cells and hippocampal neurons induced by adenoviral-mediated FAD human amyloid precursor protein gene expression

Abstract: We used adenoviral-mediated gene transfer of human amyloid precursor proteins (h-APPs) to evaluate the role of various h-APPs in causing neuronal cell death. We were able to infect PC12 cells with very high efficiency because approximately 90% of the cells were cytochemically positive for beta-galactosidase activity when an adenoviral vector containing LacZ cDNA was used to infect cells. Cells infected with adenovirus containing h-APP cDNA showed high-level transcription and expression of h-APP as measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 92 publications
(90 reference statements)
1
11
0
Order By: Relevance
“…We utilized a screening method termed 'Death trap' that selects genes from a cDNA library on the basis of survival of cDNA-transfected cells, despite of cytotoxic mechanism, under a certain cell deathcausing insult [79]. We used the London-type APP mutant, V642I-APP as the AD-specific insult [59], since the expression of V642I-APP induces cell death in neuronal cell lines and primary cortical neurons in vitro [15,23,47,59,60,64,85,87,92]. As the result of the functional screening, we isolated a group of cDNA clones that encoded a novel 24 Fig (2).…”
Section: Humanin Is a Neuroprotective Factormentioning
confidence: 99%
“…We utilized a screening method termed 'Death trap' that selects genes from a cDNA library on the basis of survival of cDNA-transfected cells, despite of cytotoxic mechanism, under a certain cell deathcausing insult [79]. We used the London-type APP mutant, V642I-APP as the AD-specific insult [59], since the expression of V642I-APP induces cell death in neuronal cell lines and primary cortical neurons in vitro [15,23,47,59,60,64,85,87,92]. As the result of the functional screening, we isolated a group of cDNA clones that encoded a novel 24 Fig (2).…”
Section: Humanin Is a Neuroprotective Factormentioning
confidence: 99%
“…However, some evidence that has been largely ignored indicates that mutant AD genes induce cell death when expressed in cell lines. Single mutations of the APP gene in AD induce cell death when expressed in differentiated PC12 cells and in primary rodent cortical neurons [108][109][110][111]. Microarray analysis in the APP Swedish transgenic mouse identifies early changes in mitochondrial metabolism and apoptotic genes [112].…”
Section: Initiating Ad Insultsmentioning
confidence: 99%
“…Although it has been generally accepted that increased production of amyloid-h (Ah) peptides from APP is closely linked to the AD pathogenesis (Hardy and Selkoe, 2002), it has not been completely understood how mutations in these genes contribute to neuronal loss in FAD brain in vivo. Multiple groups (Yamatsuji et al, 1996a,b;Wolozin et al, 1996;Zhao et al, 1997;Nishimura et al, 1998;Luo et al, 1999;Hashimoto et al, 2000) have provided evidence that expression of FAD-associated mutant APP and PS genes causes neuronal cell death in cultured cells. It has been found that V642 mutants (V642I/F/G) of APP and K595N/M596L-APP (NL-APP) induce cytotoxicity through the pertussis toxin (PTX)-sensitive G protein G o (Nishimoto et al, 1993;Yamatsuji et al, 1996a,b).…”
Section: Introductionmentioning
confidence: 99%